Does firm life cycle have impacts on managerial promotion tournament incentives?. Issue 4 (November 2021) - Chowdhury, Hasibul; Shams, Syed
We examine whether and how firm-level promotion tournament incentives for executives, measured by the pay gap between a chief executive officer (CEO) and non-CEO executives, vary in different corporate life-cycle stages. Results show that managerial tournament incentives are higher in growth and mature life-cycle stages than in introduction and decline stages. In additional analyses, we find that firms design compensation contracts for growth and mature life-cycle stages with a target to increase tournament incentives for non-CEO executives that induce managerial risk-taking behaviour, leading to high productivity and performance. JEL Classification:G30, M12